Tantalic acid compound dispersion and manufacturing method thereof

JP2025013552A5Active Publication Date: 2025-04-22MITSUI MINING & SMELTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024194827
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-11
Filing Date
2024-11-07
Publication Date
2025-04-22
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

Tantalum oxide sols contain organic components like oxalic acid, which hinder film formation and catalytic action, while lithium tantalate exhibits poor dispersibility and solubility in water, leading to storage instability.

Method used

A tantalic acid compound dispersion with tantalum concentration between 0.1% to 30% by mass and particle diameter of 100 nm or less, ionically bonded with organic nitrogen compounds and alkali metals, providing high dispersibility and solubility in polar solvents, especially water, and excellent storage stability.

Benefits of technology

The dispersion achieves high dispersibility and solubility in water, maintaining stability over time and forming uniform films, enhancing the performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a tantalic acid compound dispersion having high dispersibility to a polar solvent, especially water, good solubility to water, and excellent storage stability and a manufacturing method thereof.SOLUTION: A tantalic acid compound dispersion of the present invention is a tantalic acid compound dispersion containing a 0.1 mass% or over and under 30 mass% of tantalum in Ta2O5 conversion and has a tantalic acid compound particle diameter (D50) in the tantalic acid compound dispersion by dynamic light scattering of 100 nm or under. Also, a manufacturing method of a tantalic acid compound dispersion of the present invention includes a reaction step to produce a tantalum compound aqueous solution by adding hydrogen peroxide to a tantalum fluoride aqueous solution and a reverse-neutralization step to produce a tantalum-containing precipitate by adding the tantalum compound aqueous solution to an alkaline aqueous solution.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tantalic acid compound dispersion and a method for producing the same. [Background technology]

[0002] Tantalate compounds are used as materials for optoelectronics, catalysts, and the like. Patent Document 1 discloses tantalum oxide sol as a tantalate compound that is composed of uniform particles and can be stored for a long period of time as a coating agent for the surfaces of various parts. In addition, tantalate compounds, particularly lithium tantalate, have excellent optical properties, nonlinear properties, and electro-optical properties, and are used in piezoelectric elements, etc. For example, Patent Document 2 discloses composite active material particles that can reduce the battery resistance generated in an all-solid-state lithium ion battery. Lithium tantalate is listed as well as lithium niobate as one of the lithium ion conductive oxides that cover at least a part of the surface of the composite active material particles. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-143315 [Patent Document 2] JP 2018-125214 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the tantalum oxide sol disclosed in Patent Document 1 contains an organic component such as oxalic acid that is difficult to volatilize, and the organic component may be a factor that prevents the formation of a uniform film and may be a factor that inhibits the catalytic action when used as an additive for a catalyst. Furthermore, lithium tantalate has poor dispersibility and solubility in water compared to lithium niobate, and is prone to precipitates over time, and the lithium tantalate produced by the method for producing lithium niobate disclosed in Patent Document 2 had low dispersibility in water, poor solubility in water, and did not have excellent storage stability.

[0005] In view of the above problems, the present invention provides a tantalic acid compound dispersion liquid having high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability, and a method for producing the same. [Means for solving the problem]

[0006] The tantalic acid compound dispersion of the present invention, made to solve the above problems, is a tantalic acid compound dispersion containing tantalum in an amount of 0.1 mass % or more and less than 30 mass % in terms of Ta2O5, and is characterized in that the tantalic acid compound particle size (D50) in the tantalic acid compound dispersion is 100 nm or less, as measured by dynamic light scattering method. The tantalic acid compound dispersion of the present invention preferably contains tantalum in an amount of 0.1% by mass or more and less than 30% by mass in terms of Ta2O5, since this improves the dispersibility and solubility in polar solvents, particularly water. The tantalic acid compound dispersion of the present invention is more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. On the other hand, the tantalic acid compound dispersion of the present invention is more preferably 25% by mass or less, and even more preferably 20% by mass or less.

[0007] Here, the tantalum concentration in the tantalic acid compound dispersion is calculated by diluting the dispersion with dilute hydrochloric acid as necessary, and measuring the Ta weight fraction converted to tantalum oxide (Ta2O5) using ICP emission spectrometry (Agilent Technologies: AG-5110) in accordance with JIS K0116:2014. Note that the tantalic acid in the tantalic acid compound dispersion of the present invention is not necessarily present in the form of Ta2O5. The content of tantalic acid is shown in terms of Ta2O5 based on the convention for showing the tantalum concentration.

[0008] Here, it is presumed that the tantalic acid compound in the tantalic acid compound dispersion of the present invention exists in the dispersion as an ion in a state in which tantalic acid is ionic-bonded with an organic nitrogen compound, an alkali metal, or an alkaline earth metal, which will be described later. In the tantalic acid compound dispersion of the present invention, hydroxide ions exist as anions, while halide ions such as fluoride ions and chloride ions are hardly present, and the organic nitrogen compound and the alkali metal are considered to exist as cations, so tantalum is TaO3 - These tantalum atoms are believed to exist as anions such as those shown below, or as polyoxometalate (polyacid) ions in which multiple tantalum atoms are bonded to oxygen atoms.

[0009] In addition, the tantalic acid compound dispersion of the present invention also contains an ionized alkaline aqueous solution, such as ammonia, in addition to the tantalic acid compound. As will be described in detail later in the manufacturing method of the tantalic acid compound dispersion of the present invention, in the manufacturing process, a reverse neutralization method is used in which an acidic tantalum complex aqueous solution is added to an alkaline aqueous solution, such as ammonia water, to generate a tantalic acid-containing precipitate, which is a tantalum-containing precipitate slurry, such as ammonium tantalate hydrous cake, and then the tantalic acid compound dispersion of the present invention is generated, so it is considered that ammonia contains ammonium ions and exists in the dispersion as a cation.

[0010] The method for measuring the ammonia concentration present in the dispersion liquid includes a method of adding sodium hydroxide to the dispersion liquid to separate ammonia by distillation and quantifying the ammonia concentration with an ion meter, a method of quantifying the N2 content in a gasified sample with a thermal conductivity meter, the Kjeldahl method, gas chromatography (GC), ion chromatography, gas chromatography mass spectrometry (GC-MS), etc. In particular, the method of quantifying the ammonia concentration with an ion meter is preferred.

[0011] Furthermore, when the tantalic acid compound particle diameter (D50) in the tantalic acid compound dispersion liquid is 100 nm or less by dynamic light scattering, it is highly dispersible, has little change over time, is stable, and is preferable in terms of reactivity when reacting with other substances or compounding, and film uniformity when forming a film. Moreover, the tantalic acid compound particle diameter (D50) is preferably smaller, more preferably 50 nm or less, even more preferably 30 nm or less, particularly preferably 20 nm or less, even more preferably 10 nm or less, even more particularly preferably 1 nm or less, and even more particularly preferably 0.6 nm or less. Thus, the tantalic acid compound particle diameter (D50) in the tantalic acid compound dispersion liquid of the present invention is measured by dynamic light scattering, and the liquid in which the tantalic acid compound particle diameter (D50) is 100 nm or less is defined as the "tantalic acid compound dispersion liquid" of the present invention.

[0012] Here, the dynamic light scattering method is a method in which light such as laser light is irradiated onto a solution such as a suspension solution, the light scattering intensity from a group of particles undergoing Brownian motion is measured, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated in accordance with JIS Z 8828:2019 "Particle Size Analysis - Dynamic Light Scattering Method" using a Zeta Potential, Particle Size, and Molecular Weight Measurement System (Otsuka Electronics Co., Ltd.: ELSZ-2000). In addition, in order to remove dust and the like in the solution to be measured immediately before the measurement, the solution is filtered with a filter with a pore size of 1 μm, and ultrasonic treatment is performed at 28 kHz for 3 minutes with an ultrasonic cleaner (As One Co., Ltd.: VS-100III). The particle size (D50) refers to the median diameter (D50), which is the particle size that shows the 50% cumulative value of the cumulative distribution curve.

[0013] In the present invention, the "dispersion" is not limited to a dispersion in which a solute is dispersed or mixed in a solvent in a monomolecular state, but also includes an aggregate in which a plurality of molecules are attracted to each other by intermolecular interactions, such as (1) polymer molecules, (2) solvated molecules, (3) molecular clusters, and (4) colloidal particles dispersed in a solvent.

[0014] The tantalic acid compound dispersion of the present invention is characterized by containing an organic nitrogen compound. It is presumed that the tantalic acid in the tantalic acid compound dispersion of the present invention is present in the dispersion as ions in an ionic state with the organic nitrogen compound.

[0015] Examples of the organic nitrogen compound include aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds.

[0016] Examples of aliphatic amines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexylamine, cyclohexylamine, piperidine, and the like.

[0017] Examples of aromatic amines include aniline, phenylenediamine, and diaminotoluene. Examples of amino alcohols include methanolamine, ethanolamine, propanolamine, butanolamine, pentanolamine, dimethanolamine, diethanolamine, trimethanolamine, methylmethanolamine, methylethanolamine, methylpropanolamine, methylbutanolamine, ethylmethanolamine, ethylethanolamine, ethylpropanolamine, dimethylmethanolamine, dimethylethanolamine, dimethylpropanolamine, methyldimethanolamine, methyldiethanolamine, diethylmethanolamine, trishydroxymethylaminomethane, bis(2-hydroxyethyl)aminotris(hydroxymethyl)methane, and aminophenol. Examples of amino acids include alanine, arginine, aspartic acid, and EDTA. Examples of polyamines include polyamines and polyetheramines.

[0018] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, and ethyl-dimethyl-propylammonium. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , BF4 - , HSO4 - etc.

[0019] Examples of the guanidine compound include guanidine, diphenylguanidine, and ditolylguanidine. Examples of the azole compound include imidazole compounds and triazole compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole. Specific examples of the triazole compound include 1,2,4-triazole, 1,2,4-triazole-3-methyl carboxylate, and 1,2,3-benzotriazole.

[0020] Here, the organic nitrogen compound is preferably an aliphatic amine because it is highly volatile and has low toxicity. Specifically, an aliphatic amine having 1 to 4 carbon atoms is more preferable, and an aliphatic amine having 1 to 2 carbon atoms is particularly preferable. Examples of the organic nitrogen compound include methylamine and dimethylamine.

[0021] In addition, the organic nitrogen compound is preferably a quaternary ammonium, since it has high solubility and high crystallization inhibition and high sol formation inhibition. For example, tetraalkylammonium salts are preferred, tetraalkylammonium hydroxide salts are more preferred, tetramethylammonium hydroxide and tetraethylammonium are particularly preferred, and tetramethylammonium hydroxide (TMAH) is also particularly preferred.

[0022] Furthermore, the organic nitrogen compound may be a mixture of two or more selected from aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds, rather than one selected from them. For example, a mixture of two types of compounds, an aliphatic amine and a quaternary ammonium compound, is preferable in that the amount of the compound added is reduced so as not to increase toxicity, while the solubility can be increased.

[0023] Specifically, examples of such mixtures include mixtures of two organic nitrogen compounds, such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), and methylamine and dimethylamine, and mixtures of three organic nitrogen compounds, such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH).

[0024] The method for measuring the concentration of the organic nitrogen compound present in the tantalic acid compound dispersion of the present invention includes gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc. When a low-volatility organic nitrogen compound is contained, it is preferable to measure the concentration of the organic nitrogen compound by liquid chromatography (LC) or liquid chromatography-mass spectrometry (LC-MS).

[0025] The tantalic acid compound dispersion of the present invention is characterized in that it contains one or more elements M selected from the group consisting of alkali metal elements and alkaline earth metal elements. Furthermore, it is preferable that the element M is Li. It is presumed that the tantalic acid in the tantalic acid compound dispersion of the present invention is present in the dispersion as an ion in an ionic bond with one or more elements M selected from the group consisting of alkali metal elements or alkaline earth metal elements. Furthermore, it is preferable that the element M is Li. Furthermore, the element M is not limited to only one alkali metal element Li, but is preferably two alkali metal elements Li and Na or K, or three alkali metal elements Li, Na, and K. Furthermore, the element M may be one alkali metal element Na or K, or two alkali metal elements Na and K.

[0026] The tantalic acid compound dispersion of the present invention is characterized in that the concentration of tantalic acid in the tantalic acid compound dispersion is 0.1% by mass or more and 15% by mass or less in terms of Ta2O5. The tantalic acid concentration in the tantalic acid compound dispersion liquid is preferably from 0.1 to 15 mass % in terms of Ta2O5 in order to achieve both practicality and stability of the lithium tantalate dispersion liquid, more preferably from 1 to 15 mass % in terms of Ta2O5, even more preferably from 3 to 10 mass % in terms of Ta2O5, and particularly preferably from 5 to 10 mass % in terms of Ta2O5.

[0027] Here, the tantalic acid concentration in the tantalic acid compound dispersion is calculated by diluting the dispersion with dilute hydrochloric acid as necessary, and measuring the Ta weight fraction in terms of Ta2O5 using ICP emission spectrometry (Agilent Technologies: AG-5110) in accordance with JIS K0116:2014. By expressing the tantalic acid concentration in the tantalic acid compound dispersion of the present invention in terms of Ta2O5, it is possible to collectively determine the state of a plurality of oxides of tantalum. In addition, when the tantalic acid in the tantalic acid compound dispersion of the present invention is ionically bonded with an alkali metal or an alkaline earth metal, for example, a lithium tantalate salt ionically bonded with a lithium ion, the lithium concentration may be calculated by measuring the Li weight fraction in terms of Li. By specifying the tantalic acid concentration and the lithium concentration in the tantalic acid compound dispersion of the present invention, it is possible to specify the molar ratio Li / Ta of lithium (Li) and tantalum (Ta) of the lithium tantalate contained in the tantalic acid compound dispersion of the present invention.

[0028] Furthermore, the tantalic acid concentration in the tantalic acid compound dispersion of the present invention can also be expressed in terms of Ta. The above-mentioned tantalic acid concentration expressed in terms of Ta is as follows. The tantalic acid concentration in the tantalic acid compound dispersion is preferably 0.08% by mass or more and 12.3% by mass or less in terms of Ta, from the viewpoint of achieving both practicality and stability of the lithium tantalate dispersion, more preferably 0.8% by mass or more and 12.3% by mass or less in terms of Ta, further preferably 2.4% by mass or more and 8.2% by mass or less in terms of Ta, and particularly preferably 4.1% by mass or more and 8.2% by mass or less in terms of Ta.

[0029] In the tantalic acid compound dispersion of the present invention, the lithium tantalate contained in the tantalic acid compound dispersion preferably has a molar ratio Li / Ta of lithium (Li) to tantalum (Ta) of 0.8 or more and 1.5 or less. The lithium tantalate contained in the tantalic acid compound dispersion preferably has a lithium (Li) to tantalum (Ta) molar ratio Li / Ta of 0.8 or more and 1.5 or less, in terms of improving dispersibility and solubility in water, more preferably 0.8 or more and 1.3 or less, even more preferably 0.9 or more and 1.2 or less, and particularly preferably 0.9 or more and 1.1 or less.

[0030] Furthermore, the ammonia concentration in the tantalate compound dispersion liquid of the present invention containing lithium tantalate may be any concentration. For example, the ammonia concentration may be more than 0 mass% and not more than 10 mass%, may be 0.001 mass% or more and 10 mass% or less, or may be 0.003 mass% or more and 5 mass% or less.

[0031] In addition, the tantalic acid compound dispersion of the present invention preferably does not contain any organic acid. Since the tantalic acid compound dispersion of the present invention does not contain an organic acid, the polyacid ions contained in the tantalic acid compound dispersion are stabilized.

[0032] The tantalic acid compound dispersion of the present invention is characterized in that it is an aqueous dispersion. The tantalic acid compound in the tantalic acid compound dispersion of the present invention has high dispersibility in water and good solubility in water, so pure water can be used as the solvent. An organic solvent may be used as the solvent. Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, etc., and the solvent may be a mixture of these organic solvents and pure water. Examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, glycerin), acetone, etc.

[0033] The tantalic acid compound dispersion of the present invention is characterized in that the tantalic acid compound dispersion has a pH of more than 7. The pH of the tantalic acid compound dispersion of the present invention is preferably more than 7 in terms of stabilizing the polyacid ions contained in the dispersion. The pH of the tantalic acid compound dispersion of the present invention is more preferably 8 or more, even more preferably 9 or more, particularly preferably 10 or more, and even more preferably 11 or more, and may be 12 or more. In addition, it is preferable that the tantalic acid compound dispersion of the present invention does not contain an organic acid in terms of lowering the pH when the organic acid is contained in the tantalic acid compound dispersion of the present invention.

[0034] Among the tantalic acid compound dispersions of the present invention, the pH of the tantalic acid compound dispersion containing an organic nitrogen compound is preferably 10.0 to 14.1.On the other hand, among the tantalic acid compound dispersions of the present invention, the pH of the tantalic acid compound dispersion containing one or more elements M selected from the group consisting of alkali metal elements and alkaline earth metal elements is preferably 11 to 13.

[0035] Here, the pH of the tantalic acid compound dispersion of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the tantalic acid compound dispersion of the present invention and confirming that the liquid temperature has stabilized at 25°C.

[0036] The tantalic acid compound dispersion of the present invention may contain an element or a compound thereof that does not constitute the tantalic acid compound contained in the tantalic acid compound dispersion of the present invention as an additive. Examples of the additive include elements or compounds such as Li, Na, Mg, Al, Si, K, Ca, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Sn, Ba, La, and W. Examples of the compound include oxides, alkali metal salts of metal acids, alkaline earth metal salts of metal acids, chlorides, alkoxides of metal acids, and polyoxometalates. In addition, the content of the additive in the tantalic acid compound dispersion of the present invention is, when the total molar number of each element contained as an additive is X, the molar ratio X / Ta of the total molar number (X) of each element contained as an additive to tantalum (Ta) may be 0.001 to 75, 0.002 to 50, 0.01 to 40, 0.2 to 30, 0.5 to 25, 0.8 to 1.5, 0.8 to 1.3, 0.9 to 1.2, or 0.9 to 1.1. Furthermore, since the tantalic acid compound dispersion of the present invention is a uniform dispersion, even if these compounds are in a suspended state, improvement in uniformity and improvement in reactivity (reaction rate) are expected. In addition, if these compounds are dissolved in the tantalic acid compound dispersion of the present invention and become a uniform dispersion, the composite element can be in the most reactive state.

[0037] Furthermore, the tantalic acid compound dispersion of the present invention may contain components (referred to as "other components") other than the components derived from tantalum or tantalic acid, ammonia, organic nitrogen compounds, and the components derived from element M, within a range that does not impair the action and effect of the dispersion. Examples of the other components include Li, Na, Mg, Al, Si, K, Ca, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Sr, Zr, Nb, Mo, Sn, Ba, La, and W. However, the other components are not limited to these. When the tantalic acid compound dispersion of the present invention is taken as 100 mass%, the content of the other components is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. It is assumed that the tantalic acid compound dispersion of the present invention contains unavoidable impurities, which are not intended. The content of the unavoidable impurities is preferably 0.01 mass% or less.

[0038] The tantalic acid compound powder of the present invention is characterized by containing the tantalic acid compound in the above-mentioned tantalic acid compound dispersion of the present invention. The tantalic acid compound powder of the present invention includes a dried powder obtained by drying the tantalic acid compound dispersion of the present invention, for example, by vacuum drying, and a fired powder obtained by firing the obtained dried powder. The tantalic acid compound powder of the present invention also includes a tantalic acid compound powder having different physical properties such as a crystal structure, which is generated by vacuum drying or firing the tantalic acid compound dispersion of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure. The method for producing the tantalic acid compound powder of the present invention will be described later.

[0039] The tantalic acid compound film of the present invention is characterized by containing the tantalic acid compound in the above-mentioned tantalic acid compound dispersion of the present invention. The tantalic acid compound film of the present invention includes a dried film obtained by applying the tantalic acid compound dispersion of the present invention to the surface of a substrate, and then drying, for example, vacuum drying, and a fired film obtained by firing the obtained dried film. The tantalic acid compound film of the present invention also includes a tantalic acid compound film having different physical properties such as a crystal structure, which is generated by vacuum drying or firing the tantalic acid compound dispersion of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure. Since the tantalum compound, which is the raw material of the tantalic acid compound film of the present invention, has high chemical resistance, the high temperature characteristics (for example, protection from deterioration of the substrate due to heat, etc.) and chemical resistance of the substrate can be improved by covering the surface of the substrate with the tantalic acid compound film of the present invention. The manufacturing method of the tantalic acid compound film of the present invention will be described later.

[0040] The coating agent of the present invention is characterized by containing at least one of the above-mentioned tantalic acid compound dispersion of the present invention or the above-mentioned tantalic acid compound powder of the present invention. The coating agent of the present invention contains at least one of the tantalic acid compound dispersion liquid of the present invention, which has high dispersibility in water, good solubility in water, and excellent storage stability, or the tantalic acid compound powder of the present invention, and is capable of forming a uniform coating film, for example, by applying it to the surface of a positive electrode active material for a lithium ion secondary battery.

[0041] The above-mentioned tantalic acid compound dispersion of the present invention can be used as a positive electrode material for a lithium ion secondary battery or as a coating for a positive electrode. The tantalic acid compound dispersion of the present invention can be used as a positive electrode material for an all-solid-state lithium ion battery or as a coating for a positive electrode. The tantalic acid compound dispersion of the present invention is suitable as a positive electrode material for lithium ion secondary batteries or for coating positive electrodes, based on the results of a stability test over time in which the state of the dispersion is visually observed after being left to stand for one month in an incubator set at room temperature (25° C.) and a dynamic light scattering method in which the particle diameter (D50) of the tantalic acid compound particles in the dispersion over time is measured. The film-formability test also shows that the tantalic acid compound dispersion of the present invention is suitable as a positive electrode material for lithium ion secondary batteries or for coating positive electrodes.

[0042] The tantalic acid compound dispersion of the present invention is also suitable for coating the surface of a positive electrode active material for a lithium ion secondary battery. By coating the surface of a positive electrode with the positive electrode active material for a lithium ion secondary battery coated with the tantalic acid compound of the present invention, the performance of the lithium secondary battery can be improved.

[0043] The method for producing the above-mentioned tantalic acid compound dispersion of the present invention will be described below.

[0044] The method for producing a tantalum acid compound dispersion of the present invention is characterized by comprising a reaction step of adding hydrogen peroxide to an aqueous tantalum fluoride solution to produce an aqueous tantalum compound solution, and a reverse neutralization step of adding the aqueous tantalum compound solution to an alkaline aqueous solution to produce a tantalum-containing precipitate.

[0045] First, the tantalum fluoride aqueous solution can be prepared by reacting tantalum, tantalum oxide, or tantalum hydroxide with hydrofluoric acid (HF) such as an aqueous solution of hydrofluoric acid to form tantalum fluoride (H2TaF7), which is then dissolved in water.

[0046] Here, it is preferable to adjust the acidic tantalum solution containing fluoride ions, for example, the tantalum fluoride aqueous solution, to contain tantalum at 1 to 100 g / L in terms of Ta2O5 by adding water (for example, pure water). In this case, it is preferable that the tantalum concentration is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tantalum concentration is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving tantalum or tantalum oxide.

[0047] Next, in the reaction step of adding hydrogen peroxide to the tantalum fluoride aqueous solution to produce a tantalum compound aqueous solution, the hydrogen peroxide solution is added to the tantalum fluoride aqueous solution and mixed to obtain a tantalum compound aqueous solution. It is presumed that at least a portion of the obtained tantalum compound aqueous solution forms a peroxo complex.

[0048] Here, the hydrogen peroxide concentration of the hydrogen peroxide solution added to the tantalum fluoride aqueous solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.

[0049] In the reverse neutralization step of adding the obtained tantalum compound aqueous solution to an alkaline aqueous solution to produce a tantalic acid-containing precipitate, the tantalum compound aqueous solution is added to an alkaline aqueous solution, for example, ammonia water, i.e., a reverse neutralization method is used to obtain a tantalum-containing precipitate slurry. Then, fluoride ions are removed from the obtained tantalum-containing precipitate slurry to obtain a tantalum-containing precipitate from which fluoride ions have been removed.

[0050] The ammonia concentration of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, tantalum is less likely to remain undissolved, and tantalum or tantalic acid can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0051] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0052] In the reverse neutralization step, the amount of tantalum fluoride aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / Ta is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, the amount of tantalum fluoride aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, from the viewpoint of generating amines or tantalic acid compounds that dissolve in dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0053] In the reverse neutralization step, the time for adding the tantalum fluoride aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the tantalum fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tantalum fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, in the reverse neutralization step, since the acidic tantalum fluoride aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tantalum fluoride aqueous solution and the ammonia water can be used at room temperature.

[0054] In the reverse neutralization step, fluoride ions are removed from the tantalum-containing precipitate slurry obtained by the reverse neutralization method, thereby obtaining a tantalum-containing precipitate from which fluoride ions have been removed. Since fluorine compounds such as ammonium fluoride are present as impurities in the tantalum-containing precipitate slurry obtained by the reverse neutralization method, it is preferable to remove these.

[0055] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the tantalum-containing precipitate slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.

[0056] Specifically, the tantalum-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a tantalum-containing precipitate from which the fluoride ions have been removed. Note that by repeating the washing, the hydrogen peroxide added in the reaction step is also removed.

[0057] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. With such ammonia water, ammonia is suitable for fluoride ions, and unnecessary cost increases can be avoided.

[0058] The method for producing a tantalic acid compound dispersion of the present invention also includes a step of mixing the tantalum-containing precipitate produced through the above-mentioned reaction step and reverse neutralization step with an organic nitrogen compound.

[0059] The tantalum-containing precipitate from which the fluoride ions have been removed through the above-mentioned reaction process and reverse neutralization process is diluted with pure water or the like to obtain a tantalum-containing precipitate slurry from which the fluoride ions have been removed. The tantalum concentration of the tantalum-containing precipitate slurry is measured by taking a portion of the tantalum-containing precipitate slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce Ta2O5. The weight of the Ta2O5 thus produced can be measured, and the tantalum concentration of the tantalum-containing precipitate slurry can be calculated from the weight.

[0060] The tantalum-containing precipitate slurry from which the fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together and stirred at 5°C to 90°C for 0.1 to 48 hours to obtain the tantalic acid compound dispersion of the present invention.

[0061] As described above, the organic nitrogen compound to be mixed with the tantalum-containing precipitation slurry is preferably an aliphatic amine, an aromatic amine, an amino alcohol, an amino acid, a polyamine, a quaternary ammonium, a guanidine compound, or an azole compound, and more preferably an aliphatic amine and / or a quaternary ammonium compound.

[0062] From the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tantalum-containing precipitation slurry is 40 mass% or less, and more preferably 20 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tantalum-containing precipitation slurry is 0.1 mass% or more, more preferably 1 mass% or more, and may be 5 mass% or more, or may be 10 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine.

[0063] From the viewpoint of solubility, the quaternary ammonium compound is preferably mixed so that the concentration of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 40% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium compound is preferably mixed so that the concentration of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. The quaternary ammonium compound is more preferably tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).

[0064] The method for producing a tantalic acid compound dispersion of the present invention also includes a step of mixing the tantalic acid-containing precipitate produced through the above-mentioned reaction step and reverse neutralization step with a hydroxide of element M containing one or more elements M selected from the group consisting of alkali metal elements and alkaline earth metal elements. Here, the hydroxide of element M is preferably lithium hydroxide.

[0065] The tantalum-containing precipitate from which the fluoride ions have been removed through the above-mentioned reaction step and reverse neutralization step is diluted with pure water or the like to obtain a tantalum-containing precipitate slurry from which the fluoride ions have been removed. The tantalum-containing precipitate slurry from which the fluoride ions have been removed, a hydroxide of element M, for example lithium hydroxide monohydrate, and pure water are mixed and stirred at 5°C to 100°C for 0.1 to 72 hours to obtain the tantalic acid compound dispersion of the present invention. Furthermore, in order to remove the ammonia component contained in the obtained tantalic acid compound dispersion of the present invention, the following concentration adjustment step may be performed. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 to 100 hours, and then cooled to room temperature. Thereafter, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the tantalic acid concentration of the tantalic acid compound dispersion after the ammonia component is removed is equal to the tantalic acid concentration of the tantalic acid compound dispersion before the ammonia component is removed.

[0066] Specifically, the tantalic acid compound dispersion of the present invention, i.e., lithium tantalate dispersion, is obtained by mixing and stirring the obtained tantalum-containing precipitate slurry, lithium hydroxide monohydrate, and pure water so that the tantalic acid concentration of the final mixture is 0.1% by mass or more and 15% by mass or less in terms of tantalum Ta2O5, and the molar ratio Li / Ta of lithium to tantalum is 0.8 to 1.5. Also, when the element M contained in the tantalic acid compound dispersion of the present invention is one element M selected from alkali metal elements other than lithium or alkaline earth metal elements, the molar ratio M / Ta of the element M to tantalum is preferably 0.8 to 1.5, more preferably 0.8 to 1.3, even more preferably 0.9 to 1.2, and particularly preferably 0.9 to 1.1. Furthermore, even when the element M contained in the tantalic acid compound dispersion of the present invention is a plurality of elements, the molar ratio M / Ta of the element M to tantalum is preferably 0.8 to 1.5, more preferably 0.8 to 1.3, even more preferably 0.9 to 1.2, and particularly preferably 0.9 to 1.1. Specifically, this includes the case where the element M is a plurality of elements including lithium and other alkali metal elements or alkaline earth metal elements, and the case where the element M is a plurality of elements selected from alkali metal elements other than lithium or alkaline earth metals.

[0067] Next, a method for producing a tantalic acid compound powder containing a tantalic acid compound in the tantalic acid compound dispersion of the present invention will be described below.

[0068] Among the tantalic acid compound powders, a method for producing a dry powder of a tantalic acid compound involves placing the tantalic acid compound dispersion obtained by the above-mentioned method for producing a tantalic acid compound dispersion of the present invention in a static furnace and drying, for example vacuum drying, for 1 hour to 72 hours at a heating temperature of about 60°C to 200°C, whereby the water content of the tantalic acid compound dispersion of the present invention evaporates, and a dry powder of the tantalic acid compound containing crystal particles of the tantalic acid compound contained in the tantalic acid compound dispersion of the present invention is obtained.

[0069] On the other hand, a method for producing a calcined powder of a tantalic acid compound includes vacuum-drying the tantalic acid compound dispersion liquid of the present invention as described above, placing the obtained dried powder of the tantalic acid compound in a static furnace, and calcining it in the atmosphere at a calcination temperature of 300°C or more and 1,200°C or less for a calcination time of 1 hour or more and 72 hours or less, thereby obtaining a calcined powder of the tantalic acid compound.

[0070] The above-mentioned dried powder and sintered powder of the tantalic acid compound may be pulverized and used as the tantalic acid compound powder. Regardless of whether or not the powder is pulverized, the above-mentioned dried powder and sintered powder of the tantalic acid compound may be classified using a sieve, and the undersize (fine grain side) obtained may be used as the tantalic acid compound powder. The oversize (coarse grain side) may be pulverized again and classified for use. It is also possible to combine pulverization and classification using a vibrating sieve into which iron balls coated with nylon or fluororesin are charged as pulverizing media. By combining classification and pulverization in this way, even if there is a tantalic acid compound powder that is too large, it is possible to remove it. Specifically, when classifying using a sieve, it is preferable to use one with an opening of 150 μm to 1,000 μm. If the particle size is 150 μm to 1,000 μm, the proportion of oversized particles will not be too high, so that re-pulverization will not be repeated, and the tantalic acid compound powder that requires re-pulverization will not be classified as undersized particles.

[0071] The tantalic acid compound powder thus obtained is mixed with water or an organic solvent as a dispersion medium, and wet-pulverized using a medium such as beads to obtain a tantalic acid compound powder dispersion. Here, examples of the organic solvent used as the dispersion medium include alcohols, esters, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, and mixed solvents thereof. Furthermore, in order to improve the film-forming properties of the tantalic acid compound film using the tantalic acid compound powder dispersion, a binder such as a resin component may be added. Examples of the resin component used as a binder include acrylic resin, polyurethane, epoxy resin, polystyrene, polycarbonate, glycol resin, cellulose resin, and mixed resins and copolymer resins thereof.

[0072] Further, a method for producing a tantalic acid compound film containing a tantalic acid compound in the tantalic acid compound dispersion of the present invention will be described below.

[0073] Among the tantalic acid compound films, a method for producing a tantalic acid compound dry film includes a coating step of coating a tantalic acid compound dispersion onto a surface of a substrate, and a film drying step of drying the tantalic acid compound dispersion coated onto the surface of the substrate to obtain a dry film.

[0074] Specifically, the tantalic acid compound dispersion obtained by the above-mentioned method for producing the tantalic acid compound dispersion of the present invention is dropped onto the surface of the substrate using a syringe while being filtered, for example, with a filter having a pore size of 1 μm, as necessary, and then applied by spin coating (1,500 rpm, 30 seconds).Then, the substrate is dried at 110° C. for 30 minutes to form a tantalic acid compound dry film on the surface of the substrate.

[0075] Of the tantalic acid compound films, a method for producing a tantalic acid compound fired film includes a coating step of coating a tantalic acid compound dispersion onto the surface of a substrate, a film drying step of drying the tantalic acid compound dispersion coated on the surface of the substrate under atmospheric pressure or under vacuum to obtain a dried film, and a film firing step of firing the dried film under atmospheric pressure at a firing temperature of 300°C or higher and 1,200°C or lower for a firing time of 1 hour or higher and 12 hours or lower to obtain a fired film.

[0076] Specifically, as described above, the tantalic acid compound dispersion is applied to the surface of a substrate, and the substrate on which a tantalic acid compound dry film is formed by drying is placed in a static furnace and baked in air at a baking temperature of 300°C or more and 1,200°C or less for a baking time of 1 hour or more and 12 hours or less, thereby forming a tantalic acid compound baked film on the surface of the substrate.

[0077] Further, a method for producing the positive electrode active material for a lithium ion secondary battery coated with the above-mentioned tantalic acid compound dispersion of the present invention will be described below.

[0078] The method for producing a positive electrode active material for a lithium ion secondary battery coated with a tantalic acid compound dispersion of the present invention is characterized by comprising: a step of mixing the tantalic acid compound dispersion of the present invention, a positive electrode active material, and, if necessary, an aqueous lithium hydroxide solution to produce a positive electrode active material slurry for a battery containing a tantalic acid compound; and a step of drying the positive electrode active material slurry for a battery containing the tantalic acid compound.

[0079] First, a battery positive electrode active material, for example, LiMn2O4 (manufactured by Merck: spinel type, particle size <0.5 μm) is added to a lithium tantalate dispersion obtained by diluting the lithium tantalate dispersion, which is the tantalic acid compound dispersion of the present invention, with pure water, to obtain a slurry containing lithium tantalate. Then, while stirring the slurry containing lithium tantalate, a lithium hydroxide aqueous solution is dropped and the slurry is kept at 90° C. for 10 minutes, to produce a battery positive electrode active material slurry containing lithium tantalate.

[0080] In addition to the above-mentioned LiMn2O4, other positive electrode active materials for batteries include LiCoO2, LiNiO2, LiFeO2, Li2MnO3, LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, LiNi 0.5 Mn 1.5 O4, LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 O2, LiCo 0.2 Ni 0.4 Mn 0.4 O2, Lithium Molybdate, LiMnO4, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMnO2, etc. can be used.

[0081] Next, the lithium tantalate-containing battery positive electrode active material slurry is dried in an atmospheric drying furnace for 15 hours while maintaining the furnace temperature at 110° C., thereby producing a lithium ion secondary battery positive electrode active material coated with lithium tantalate. In addition to the above-mentioned production methods, the lithium ion secondary battery positive electrode active material coated with the tantalic acid compound dispersion of the present invention may be produced by a dipping method, a spray atomization method, a fluidized bed method, a circulating fluidized bed method, a tumbling fluidized bed method, a coprecipitation method, or the like.

[0082] In the positive electrode active material for a lithium ion secondary battery coated with the above-mentioned lithium tantalate dispersion liquid, the lithium tantalate dispersion liquid of the present invention was used, but a dried powder obtained by drying the lithium tantalate dispersion liquid of the present invention, or a calcined powder obtained by drying and calcining the lithium tantalate dispersion liquid of the present invention and dispersing the calcined powder in a dispersion medium may also be used.

[0083] In the above-mentioned method for producing a positive electrode active material for a lithium ion secondary battery, the positive electrode active material for a battery is added, but it may be changed according to the application. For example, a dispersant, a pH adjuster, a colorant, a thickener, a wetting agent, a binder resin, etc. may be added.

[0084] In the above-mentioned method for producing a positive electrode active material for a lithium ion secondary battery, the lithium tantalate dispersion liquid of the present invention is used, but it may be replaced with a tantalic acid compound dispersion liquid of the present invention containing an organic nitrogen compound, and a positive electrode active material for a lithium ion secondary battery coated with tantalic acid can be produced through similar steps.

[0085] In this manner, by coating the surface of the positive electrode active material particles for a lithium ion secondary battery with the tantalic acid compound dispersion liquid of the present invention, the interfacial resistance occurring between the positive electrode of the lithium ion secondary battery and the electrolyte of the positive electrode active material particles of the secondary battery can be reduced.

[0086] Furthermore, for the purpose of reducing the interface resistance occurring between the positive electrode of a lithium ion secondary battery and the electrolyte of the positive electrode active material particles of the secondary battery, the surface of the positive electrode active material particles for the lithium ion secondary battery may be coated with a tantalic acid compound dispersion obtained by mixing the tantalic acid compound dispersion of the present invention with a niobic acid compound, for example, lithium niobate or niobic acid. Note that the tantalic acid compound particle diameter (D50) by dynamic light scattering method in the tantalic acid compound dispersion obtained by mixing the tantalic acid compound dispersion of the present invention with a niobic acid compound, or the niobic acid compound particle diameter (D50) is preferably 100 nm or less.

[0087] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention

[0088] The tantalic acid compound dispersion of the present invention has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. BEST MODE FOR CARRYING OUT THEINVENTION

[0089] The tantalic acid compound dispersion according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.

[0090] Example 1 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of a 55 mass% aqueous hydrofluoric acid solution, and 849 mL of ion-exchanged water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 concentration 8.2 mass%).

[0091] 27.5 g of hydrogen peroxide solution (H2O2 concentration 35 mass %) was added to 1,000 g of this tantalum fluoride aqueous solution (H2O2 / Ta molar ratio = 0.76) and stirred for 5 minutes to obtain an aqueous tantalum compound solution.

[0092] 1,000 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 10 minutes (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.7) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of tantalic acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.

[0093] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.

[0094] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.

[0095] Then, the tantalum-containing precipitate slurry diluted with pure water, 5 mass% dimethylamine as an organic nitrogen compound, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the weight ratio of Ta2O5 / organic nitrogen compound was 1.0, thereby obtaining a tantalic acid compound dispersion liquid according to Example 1. The pH of the tantalic acid compound dispersion liquid according to Example 1 was 12.0.

[0096] Example 2 In Example 2, the same manufacturing method as in Example 1 was carried out, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 20 mass% methylamine, and the weight ratio of Ta2O5 / organic nitrogen compound was 4.0, to obtain a tantalic acid compound dispersion according to Example 2. The pH of the tantalic acid compound dispersion according to Example 2 was 12.9.

[0097] Example 3 In Example 3, the same manufacturing method as in Example 1 was carried out, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 5 mass% tetramethylammonium hydroxide (TMAH), to obtain a tantalic acid compound dispersion according to Example 3. The pH of the tantalic acid compound dispersion according to Example 3 was 13.3.

[0098] Example 4 In Example 4, the same manufacturing method as in Example 1 was carried out, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 1 mass% dimethylamine, and the tantalum concentration of the final mixture was 1 mass% in terms of Ta2O5, to obtain a tantalic acid compound dispersion according to Example 4. The pH of the tantalic acid compound dispersion according to Example 4 was 11.4.

[0099] Example 5 In Example 5, the same manufacturing method as in Example 1 was carried out, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 10 mass% dimethylamine, and the tantalum concentration of the final mixture was 10 mass% in terms of Ta2O5, to obtain a tantalic acid compound dispersion according to Example 5. The pH of the tantalic acid compound dispersion according to Example 5 was 12.2.

[0100] Example 6 In Example 6, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 6, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 10 mass% tetramethylammonium hydroxide (TMAH) and the tantalum concentration of the final mixture was 10 mass% calculated as Ta2O5. The pH of the tantalic acid compound dispersion according to Example 6 was 13.9.

[0101] Example 7 In Example 7, a tantalic acid compound dispersion liquid according to Example 7 was obtained by carrying out the same manufacturing method as in Example 1, except that hydrogen peroxide water (H2O2 concentration 35 mass %) was added to the tantalum fluoride aqueous solution so that the H2O2 / Ta molar ratio was 0.9. The pH of the tantalic acid compound dispersion liquid according to Example 7 was 11.9.

[0102] Example 8 In Example 8, a tantalic acid compound dispersion liquid according to Example 8 was obtained by carrying out the same manufacturing method as in Example 1, except that hydrogen peroxide water (H2O2 concentration 35 mass %) was added to the tantalum fluoride aqueous solution so that the H2O2 / Ta molar ratio was 0.70. The pH of the tantalic acid compound dispersion liquid according to Example 8 was 12.0.

[0103] Example 9 In Example 9, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 9, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 20 mass% dimethylamine, the tantalum concentration of the final mixture was 12 mass% in terms of Ta2O5, and the weight ratio of Ta2O5 / organic nitrogen compound was 1.7. The pH of the tantalic acid compound dispersion according to Example 9 was 12.5.

[0104] Example 10 In Example 10, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 10, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 12 mass% tetramethylammonium hydroxide (TMAH), the tantalum concentration of the final mixture was 20 mass% in terms of Ta2O5, and the weight ratio of Ta2O5 / organic nitrogen compound of the final mixture was 0.6. The pH of the tantalic acid compound dispersion according to Example 10 was 14.1.

[0105] Example 11 In Example 11, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 11, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 4 mass% dimethylamine, and the weight ratio of Ta2O5 / organic nitrogen compound in the final mixture was 0.8. The pH of the tantalic acid compound dispersion according to Example 11 was 11.8.

[0106] Example 12 In Example 12, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 12, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 40 mass% dimethylamine, the tantalum concentration of the final mixture was 1 mass% in terms of Ta2O5, and the weight ratio of Ta2O5 / organic nitrogen compound was 40.0. The pH of the tantalic acid compound dispersion according to Example 12 was 13.4.

[0107] Example 13 In Example 13, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 13, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 35 mass% dimethylamine, and the weight ratio of Ta2O5 / organic nitrogen compound in the final mixture was 7.0. The pH of the tantalic acid compound dispersion according to Example 13 was 13.0.

[0108] Example 14 In Example 14, the same manufacturing method as in Example 1 was carried out to obtain a tantalic acid compound dispersion according to Example 14, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was a mixture of three organic nitrogen compounds, namely, 4 mass% dimethylamine, 0.5 mass% methylamine, and 0.5 mass% tetramethylammonium hydroxide (TMAH), and the weight ratios of Ta2O5 / organic nitrogen compound in the final mixture were 0.8, 0.1, and 0.1, respectively. The pH of the tantalic acid compound dispersion according to Example 14 was 12.1.

[0109] Comparative Example 1 In Comparative Example 1, a tantalic acid compound dispersion according to Comparative Example 1 was obtained by carrying out the same production method as in Example 1, except that the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 30 mass% dimethylamine, and the tantalum concentration of the final mixture was 30 mass% calculated as Ta2O5. The pH of the tantalic acid compound dispersion according to Comparative Example 1 was 12.7.

[0110] Comparative Example 2 In Comparative Example 2, a tantalic acid compound dispersion according to Comparative Example 2 was obtained by carrying out the same production method as in Example 1, except that hydrogen peroxide water was not added to the tantalum fluoride aqueous solution and the weight ratio of Ta2O5 / organic nitrogen compound in the final mixture was 1.0. The pH of the tantalic acid compound dispersion according to Comparative Example 2 was 12.0.

[0111] Comparative Example 3 In Comparative Example 3, the same production method as in Example 1 was carried out, except that no hydrogen peroxide solution was added to the tantalum fluoride aqueous solution, and no organic nitrogen compound was added to the tantalum-containing precipitate slurry diluted with pure water, to obtain a tantalic acid compound dispersion according to Comparative Example 3. The pH of the tantalic acid compound dispersion according to Comparative Example 3 was 10.7.

[0112] Comparative Example 4 The tantalic acid compound dispersion liquid according to Comparative Example 4 was produced as follows.

[0113] 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of a 55 mass% aqueous hydrofluoric acid solution, and 849 mL of ion-exchanged water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 concentration 8.2 mass%).

[0114] 100 g of this tantalum fluoride aqueous solution was added to 100 mL of 50 mass% dimethylamine in less than 10 minutes. After that, the mixture was stirred for 15 minutes to obtain a first reaction liquid (pH 11). This first reaction liquid was added to 2 L of ammonia water (NH3 concentration 25 mass%) in less than 10 minutes to obtain a second reaction liquid (pH 11). This second reaction liquid was a slurry of tantalum acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.

[0115] Next, this secondary reaction liquid was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed. At this time, ammonia water was used as the washing liquid.

[0116] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.

[0117] Then, the tantalum-containing precipitate slurry diluted with pure water, 5 mass% dimethylamine as an organic nitrogen compound, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the weight ratio of Ta2O5 / organic nitrogen compound was 1.0, thereby obtaining a tantalic acid compound dispersion liquid according to Comparative Example 4. The pH of the tantalic acid compound dispersion liquid according to Comparative Example 4 was 12.0.

[0118] Comparative Example 5 In Comparative Example 5, the organic nitrogen compound mixed with the tantalum-containing precipitate slurry diluted with pure water was 10 mass% dimethylamine, and the tantalum concentration of the final mixture was 10 mass% calculated as Ta2O5, but the same production method as in Comparative Example 4 was carried out to obtain a tantalic acid compound dispersion according to Comparative Example 5. The pH of the tantalic acid compound dispersion according to Comparative Example 5 was 12.1.

[0119] Example 15 The tantalic acid compound dispersion liquid according to Example 15 was produced as follows.

[0120] 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of a 55 mass% aqueous hydrofluoric acid solution, and 849 mL of ion-exchanged water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 concentration 8.2 mass%).

[0121] To 1,000 g of this tantalum fluoride aqueous solution, 36.1 g of hydrogen peroxide solution (H2O2 concentration 35 mass %) was added (H2O2 / Ta molar ratio = 1.0), and the mixture was stirred for 5 minutes to obtain an aqueous tantalum compound solution.

[0122] 1,000 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 1 minute (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.7) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of tantalic acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.

[0123] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.

[0124] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.

[0125] Then, the tantalum-containing precipitate slurry diluted with pure water, 0.54 mass% lithium hydroxide, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the molar ratio of Li / Ta was 1.0, thereby obtaining a tantalic acid compound dispersion liquid according to Example 15. The pH of the tantalic acid compound dispersion liquid according to Example 15 was 12.2, and the ammonia concentration was 0.7 mass%.

[0126] (Example 16) In Example 16, a tantalic acid compound dispersion according to Example 16 was obtained by carrying out the same production method as in Example 15, except that the tantalum concentration in the final mixture was 1 mass% in terms of Ta2O5. The tantalic acid compound dispersion according to Example 16 had a pH of 11.9 and an ammonia concentration of 0.2 mass%.

[0127] (Example 17) In Example 17, a tantalic acid compound dispersion according to Example 17 was obtained by carrying out the same production method as in Example 15, except that the tantalum concentration in the final mixture was 10 mass% in terms of Ta2O5. The tantalic acid compound dispersion according to Example 17 had a pH of 12.3 and an ammonia concentration of 1.5 mass%.

[0128] (Example 18) In Example 18, a tantalic acid compound dispersion according to Example 18 was obtained by carrying out the same production method as in Example 15, except that the molar ratio of Li / Ta in the final mixture was 0.8. The pH of the tantalic acid compound dispersion according to Example 18 was 12.0, and the ammonia concentration was 0.7 mass%.

[0129] (Example 19) In Example 19, a tantalic acid compound dispersion according to Example 19 was obtained by carrying out the same production method as in Example 15, except that the molar ratio of Li / Ta in the final mixture was 1.5. The pH of the tantalic acid compound dispersion according to Example 19 was 12.4, and the ammonia concentration was 0.7 mass%.

[0130] (Example 20) In Example 20, the tantalic acid compound dispersion obtained in Example 15 was heated to 70°C in a water bath, held for 10 hours while stirring, and then cooled to room temperature. In order to replenish the moisture evaporated by this heating, pure water was added and the concentration was adjusted so that the tantalum concentration was 5 mass% in terms of Ta2O5, thereby obtaining a tantalic acid compound dispersion according to Example 20. The pH of the tantalic acid compound dispersion according to Example 20 was 11.8, and the ammonia concentration was 0.02 mass%.

[0131] Example 21 In Example 21, the tantalic acid compound dispersion obtained in Example 15 was heated to 80°C in a water bath, held for 10 hours with stirring, and then cooled to room temperature. In order to replenish the moisture evaporated by this heating, pure water was added and the concentration was adjusted so that the tantalum concentration was 5 mass% in terms of Ta2O5, thereby obtaining a tantalic acid compound dispersion according to Example 20. The pH of the tantalic acid compound dispersion according to Example 21 was 11.7, and the ammonia concentration was 0.006 mass%.

[0132] Comparative Example 6 In Comparative Example 6, a tantalic acid compound dispersion according to Comparative Example 6 was obtained by carrying out the same production method as in Example 15, except that the tantalum concentration in the final mixture was 15 mass% in terms of Ta2O5. The pH of the tantalic acid compound dispersion according to Comparative Example 6 was not measurable.

[0133] Comparative Example 7 The tantalic acid compound dispersion liquid according to Comparative Example 7 was produced as follows.

[0134] To 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd., 1,824 g of pure water and 1,285 g of hydrogen peroxide solution (H2O2 concentration 35 mass%) were added (H2O2 / Ta molar ratio = 32.1) and stirred for 0.5 hours to obtain a tantalum-containing dispersion liquid.

[0135] Next, 3,246.9 g of this tantalum-containing dispersion was added to 168.4 mL of ammonia water (NH3 concentration: 25% by mass) over a period of less than 10 minutes (NH3 / Ta molar ratio: 6.0) to obtain a reaction liquid (pH 11).

[0136] Then, this reaction liquid was mixed with 0.289 mass% lithium hydroxide so that the tantalum concentration in the final mixture was 2.7 mass% in terms of Ta2O5 and the molar ratio of Li / Ta was 1.0, thereby obtaining a tantalic acid compound dispersion liquid according to Comparative Example 7. The pH of the tantalic acid compound dispersion liquid according to Comparative Example 7 was 12.1.

[0137] Comparative Example 8 In Comparative Example 8, a tantalic acid compound dispersion liquid according to Comparative Example 8 was obtained by carrying out the same production method as in Comparative Example 7, except that hydrogen peroxide water was added to tantalum hydroxide so that the H2O2 / Ta molar ratio was 1.0. The pH of the tantalic acid compound dispersion liquid according to Comparative Example 8 was 12.1.

[0138] Comparative Example 9 In Comparative Example 9, the same production method as in Example 15 was carried out except that hydrogen peroxide water was not added to the tantalum fluoride aqueous solution, to obtain a tantalic acid compound dispersion according to Comparative Example 9. The pH of the tantalic acid compound dispersion according to Comparative Example 9 was 12.2.

[0139] Comparative Example 10 The tantalic acid compound dispersion liquid according to Comparative Example 10 was produced as follows.

[0140] 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of a 55 mass% aqueous hydrofluoric acid solution, and 849 mL of ion-exchanged water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 concentration 8.2 mass%).

[0141] 100 g of this tantalum fluoride aqueous solution was added to 100 mL of 50 mass% dimethylamine in less than 10 minutes. After that, the mixture was stirred for 15 minutes to obtain a first reaction liquid (pH 11). This first reaction liquid was added to 2 L of ammonia water (NH3 concentration 25 mass%) in less than 10 minutes to obtain a second reaction liquid (pH 11). This second reaction liquid was a slurry of tantalum acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.

[0142] Next, this secondary reaction liquid was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed. At this time, ammonia water was used as the washing liquid.

[0143] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.

[0144] Then, the tantalum-containing precipitate slurry diluted with pure water, 0.54 mass% lithium hydroxide, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the molar ratio of Li / Ta was 1.0, thereby obtaining a tantalic acid compound dispersion liquid according to Comparative Example 10. The pH of the tantalic acid compound dispersion liquid according to Comparative Example 10 was 12.2.

[0145] The following physical properties were measured for the tantalic acid compound dispersions of Examples 1 to 21 and Comparative Examples 1 to 10. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results for the tantalic acid compound dispersions of Examples 1 to 10 and Comparative Examples 1 to 5 are shown in Table 1, and the measurement results for the tantalic acid compound dispersions of Examples 15 to 21 and Comparative Examples 6 to 10 are shown in Table 2.

[0146] <Elemental analysis> If necessary, the sample was appropriately diluted with dilute hydrochloric acid, and using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014, the Ta weight fraction in Ta2O5 terms was measured for the tantalic acid compound dispersions of Examples 1 to 14 and Comparative Examples 1 to 5, and the Ta weight fraction in Ta2O5 terms or the Li weight fraction in Li terms was measured for the tantalic acid compound dispersions of Examples 15 to 21 and Comparative Examples 6 to 10.

[0147] Quantitative analysis of ammonia 25 ml of sodium hydroxide solution (30 g / 100 ml) was added to 1 to 5 ml of the sample solution, and the mixture was boiled and distilled. The distillate (about 200 ml) was poured into a container containing 20 ml of pure water and 0.5 ml of sulfuric acid to separate ammonia. Next, the separated ammonia was transferred to a 250 ml measuring flask and the volume was adjusted to 250 ml with pure water. Furthermore, 10 ml of the solution adjusted to 250 ml was taken into a 100 ml measuring flask, 1 ml of sodium hydroxide solution (30 g / 100 mL) was added to the taken solution, and the volume was adjusted to 100 ml with pure water. The solution thus obtained was quantitatively analyzed using an ion meter (main body: HORIBA F-53, electrode: HORIBA 500 2A) to measure the ammonia concentration (mass%) contained in the tantalic acid compound dispersion liquid of Examples 15 to 21.

[0148] <pH measurement> After confirming that the temperature of the electrode (HORIBA: Standard ToupH electrode 9615S-10D) of the pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) was stable at 25°C, the pH of the tantalum acid compound dispersions according to Examples 1 to 21 and Comparative Examples 1 to 10 was measured.

[0149] 〈Dynamic light scattering method〉 The evaluation of the particle size distribution was performed by the dynamic light scattering method according to JIS Z 8828:2019 using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000). Also, immediately before the measurement, in order to remove dust and the like in the tantalum acid compound dispersions according to Examples 1 to 21 and Comparative Examples 1 to 10, which were the measurement targets, the dispersions were filtered through a filter with a pore size of 1 μm for filtering. Then, ultrasonic treatment was performed for 3 minutes at 28 kHz using an ultrasonic cleaner (manufactured by AS ONE: VS-100III) for dispersion treatment using ultrasonic waves. Furthermore, D50 indicates the particle size at which the volume fraction reaches 50%. "Initial particle size D50 (nm)" in Table 1 refers to the tantalum acid compound particle size (D50) in the tantalum acid compound dispersion immediately after generation. Also, "Particle size D50 (nm) over time" in Table 1 refers to the tantalum acid compound particle size (D50) in the tantalum acid compound dispersion after standing in a thermostat set at room temperature of 25°C for 1 month. Then, the measured "Initial particle size D50 (nm)" and "Particle size D50 (nm) over time" were evaluated according to the evaluation criteria "A", "B", "C", or "D". Evaluation criterion "A" indicates those that satisfy "D50 ≤ 10 nm". Evaluation criterion "B" indicates those that satisfy "10 nm < D50 ≤ 50 nm". Evaluation criterion "C" indicates those that satisfy "50 nm < D50 ≤ 100 nm". Evaluation criterion "D" indicates those that satisfy "100 nm < D50". Note that the above-mentioned filtering was performed during the measurement of "Initial particle size D50 (nm)", but not during the measurement of "Particle size D50 (nm) over time", and only ultrasonic treatment was performed.

[0150] 〈Stability test over time〉 The tantalic acid compound dispersions according to Examples 1 to 21 and Comparative Examples 1 to 10 were left to stand for one month in an incubator set at room temperature of 25°C, and then the presence or absence of white precipitation and gelation was visually observed. Those in which no white precipitation or gelation was observed were evaluated as having temporal stability and were marked with "○", and those in which even one white precipitation or gelation was observed were evaluated as not having temporal stability and were marked with "×". Here, gelation was judged by placing each tantalic acid compound dispersion in a plastic container, and turning the container upside down, and judging that the dispersion did not fall quickly as gelling. In addition, the particle diameter (D50) of the tantalic acid compound in the tantalic acid compound dispersions of Examples 1 to 21 and Comparative Examples 1 to 10 after standing for one month was measured using the dynamic light scattering method described above.

[0151] <Film-forming test> The appearance of the coating film formed on the surface of the glass substrate, which is a substitute for the current collector, was evaluated by observing it with an optical microscope. The tantalic acid compound dispersion liquid according to Examples 1 to 21 and Comparative Examples 1 to 10 was dropped onto a 50 mm x 50 mm glass substrate that had been degreased and washed with acetone and dried using a syringe while being filtered with a filter having a pore size of 2 μm, and was applied by spin coating (1,500 rpm, 15 seconds). The applied portion was then naturally dried to form a coating film on the glass substrate. The glass substrate was observed with an optical microscope (magnification: 40 times) in a central area of ​​15 mm x 15 mm of the formed coating film. When no bubbles, uneven coating, or cracks were observed, the glass substrate was evaluated as having excellent film-forming properties and was evaluated as "○", and when even one was observed, the glass substrate was evaluated as not having excellent film-forming properties and was evaluated as "×".

[0152] [Table 1]

[0153] [Table 2]

[0154] As shown in Table 1, the tantalic acid compound dispersions according to Examples 1 to 14 contained tantalum in an amount of 0.1% by mass or more and less than 30% by mass in terms of Ta2O5, and had a particle size (D50) of the tantalic acid compound in the dispersion of 100 nm or less as measured by dynamic light scattering, and had high dispersibility in the dispersion medium and excellent solubility. The tantalic acid compound dispersions according to Examples 15 to 21 contained tantalum in an amount of 0.1% by mass or more and less than 30% by mass in terms of Ta2O5, and had a particle size (D50) of the tantalic acid compound in the dispersion of 100 nm or less as measured by dynamic light scattering, and had high dispersibility in the dispersion medium and excellent solubility.

[0155] In the tantalic acid compound dispersions according to Examples 1 to 21, the particle diameter (D50) of the tantalic acid compound over time was not significantly different from the initial particle diameter (D50) even after one month had passed, and the tantalic acid compound dispersions according to Comparative Examples 1 to 3 and 7 to 10 showed a precipitate. In addition, the initial particle diameter (D50) and the particle diameter (D50) over time of the tantalic acid compound in the tantalic acid compound dispersions according to Comparative Examples 4 and 5 were 100 nm or more, and the stability over time was also poor. Furthermore, the initial particle diameter (D50) and the particle diameter (D50) over time of the tantalic acid compound in the tantalic acid compound dispersion according to Comparative Example 6 could not be measured due to gelation.

[0156] In the tantalic acid compound dispersions of Examples 15 to 21, when the molar ratio Li / Ta of lithium to tantalum was 0.8 or more and 2.0 or less, and the tantalic acid concentration in the dispersion was 0.1% by mass or more and 15% by mass or less in terms of tantalum Ta2O5, the stability during long-term storage was improved.

[0157] The tantalic acid compound dispersions according to Examples 1 to 21 were excellent in stability over time when the pH of the dispersions exceeded 7. The tantalic acid compound dispersion according to Comparative Example 6 was gelled, and the pH could not be measured.

[0158] The tantalic acid compound films formed from the tantalic acid compound dispersions of Examples 1 to 21 were observed under an optical microscope to show that the coating films formed from each tantalic acid compound dispersion contained no coarse particles, and no air bubbles, coating unevenness, or cracks were observed, indicating that the films had excellent film-forming properties.

[0159] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]

[0160] The tantalic acid compound dispersion according to the present invention is suitable for coating the positive electrode active material of a lithium ion secondary battery because it has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. In addition, the tantalic acid compound dispersion according to the present invention has excellent storage stability and can suppress the rate of defective products caused by precipitation due to changes over time, so that waste can be reduced and the energy cost for waste disposal can be reduced. Furthermore, the tantalic acid compound dispersion according to the present invention also has good film formation, so that waste can be reduced in the same way in the positive electrode active material of the coated lithium ion secondary battery, and the rate of defective products can be suppressed. These points lead to the achievement of sustainable management and efficient benefits of natural resources, as well as decarbonization (carbon neutralization).

Claims

1. A tantalum compound dispersion containing tantalum, A tantalum compound dispersion comprising a lithium element contained in the tantalum compound dispersion.

2. The tantalum compound dispersion liquid described in claim 1, characterized in that the molar ratio Li / Ta of lithium (Li) to tantalum (Ta) in the tantalum compound dispersion liquid is 0.8 or more and 1.5 or less.

3. A tantalum compound dispersion containing tantalum, A tantalum compound dispersion comprising an organic nitrogen compound contained in the tantalum compound dispersion.

4. The tantalum compound dispersion liquid as described in claim 3, characterized in that the content of the organic nitrogen compound is 0.1 mass% or more and 40 mass% or less.

5. The tantalum compound dispersion liquid described in any one of claims 1 to 4, characterized in that the tantalum compound dispersion liquid contains a tantalum compound, and the tantalum compound is a tantalic acid compound.

6. The tantalum compound dispersion liquid described in any one of claims 1 to 4, characterized in that the tantalum compound is contained in the tantalum compound dispersion liquid, and the tantalum compound is a polyacid compound.

7. 5. The tantalum compound dispersion according to claim 1, wherein the tantalum compound dispersion is an aqueous dispersion.

8. 5. The tantalum compound dispersion according to claim 1, wherein the tantalum compound dispersion has a pH of 8 or more.

9. The tantalum compound dispersion liquid according to claim 1, wherein the tantalum content is equal to or greater than 0.1 mass % and less than 30 mass % in terms of Ta 2 O 5 .

10. A tantalum compound powder, which is a dried powder and / or a calcined powder of the tantalum compound dispersion liquid according to any one of claims 1 to 4.

11. A tantalum compound film, which is a coating of the tantalum compound dispersion liquid according to any one of claims 1 to 4.

12. A coating agent comprising the tantalum compound dispersion liquid according to any one of claims 1 to 4.

13. 5. A positive electrode active material for a lithium ion secondary battery, the surface of which is coated with the tantalum compound contained in the tantalum compound dispersion liquid according to claim 1.

14. A lithium ion secondary battery comprising a positive electrode coated with the positive electrode active material according to claim 13.